Drosophila VCP/p97 Mediates Dynein-Dependent Retrograde Mitochondrial Motility in Axons - Gonzalez, Ashley E.; Wang, Xinnan (Frontiers in Cell and Developmental Biology, 2020)
Valosin-containing protein (VCP), also called p97, is an evolutionarily conserved and ubiquitously expressed ATPase with diverse cellular functions. Dominant mutations in VCP are found in a late-onset multisystem degenerative proteinopathy. The neurological manifestations of the disorder include frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS). In these patients, long motor neuron axons could be particularly susceptible to defects in axonal transport. However, whether VCP has a physiological function in maintaining axonal transport and whether this role is impaired by disease-causing mutations remains elusive. Here, by employing live-imaging methods in Drosophila larval axons and performing genetic interaction experiments, we discover that VCP regulates the axonal transport of mitochondria. Downregulation of VCP enhances the retrograde transport of mitochondria and reduces the density of mitochondria in larval axons. This unidirectional motility phenotype is rescued by removing one copy of the retrograde motor dynein heavy chain (DHC), or elevating Miro which facilitates anterograde mitochondrial movement by interacting with the anterograde motor kinesin heavy chain (KHC). Importantly, Miro upregulation also significantly improves ATP production of VCP mutant larvae. We investigate human VCP pathogenic mutations in our fly system. We find that expressing these mutations affects mitochondrial transport in the same way as knocking down VCP. Our results reveal a new role of VCP in mediating axonal mitochondrial transport, and provide evidence implicating impaired mitochondrial motility in the pathophysiology of VCP-relevant neurodegenerative diseases.